135 Novel Hybrid Positron Emission Tomography - Magnetic Resonance (PET-MR) Multi-modality Inflammatory Imaging has Improved Diagnostic Accuracy for Detecting Cardiac Sarcoidosis. (31st May 2014) - Wicks, Eleanor; Menezes, Leon; Pantazis, Antonios; Mohiddin, Sam; Porter, Joanna; Booth, Helen; Sekhri, Neha; O'Meara, Celia; Moon, James; McKenna, William; Groves, Ashley; Elliott, Perry
Abstract : Background: Cardiac sarcoidosis (CS) is associated with poor outcomes, but detection remains difficult.Few studies evaluate 18-fluorodeoxyglucose positron emission tomography (PET) and cardiac magnetic resonance imaging (MRI) for CS diagnosis. None examine a novel hybrid PET-MR approach. We sought to examine the diagnostic accuracy of hybrid PET-MR imaging for CS detection. Methods: 51 consecutive patients with biopsy-proven or clinically suspected CS (age 48 ± 13 years, 32% males) underwent hybrid PET-MR imaging. 18-FDG tracer uptake and late gadolinium enhancement (LGE) were qualitatively assessed on a binary scale and quantitatively by measuring standardised uptake value (SUV) and % LGE detected in each myocardial segment. Sensitivity and specificity of PET-MR for CS diagnosis was calculated. Inter-modality agreement was performed by the Cohen κ method. Coefficient of variance (COV) was performed to determine whether SUV quantification analysis discriminated between CS presence and absence. Results: 37 (73%) of the patients had confirmed sarcoidosis; 46% were histologically proven and 59% had cardiac involvement according to JMHW guidelines. FDG uptake on PET-MR was equivalent to PET-CT (p < 0.001), confirming that simultaneous hybrid PET-MR is feasible. When considered in isolation, sensitivity of PET and MR at detecting abnormalities was 0.65 and 0.6, respectively. In contrast, hybrid imaging had improved sensitivity of 0.89 in detecting probable cardiac sarcoidosis with specificity, positive and negative predictive values of 0.42, 0.8 and 0.6, respectively. Sensitivity for detecting confirmed CS using hybrid PET-MR was 100%. Notably, there was poor inter-modality agreement between the location of increased SUV and LGE (k = 0.021). This may reflect the natural history of CS with progression from inflammation to scar and also account for the sensitivity of hybrid imaging. Coefficient of variance analysis of SUV uptake suggested that a COV above 25% predicted CS. Conclusion: This is the first study to describe the feasibility and improved diagnostic accuracy of novel hybrid cardiac PET-MR imaging in CS. This technique may allow for more accurate and earlier diagnoses and may also allow titration of therapy according to disease activity.